Strategic analysis of hub port competitiveness in the Mediterranean and Northern Europe: a focus on sustainability and efficiency - Samia Bouazza; Zoubida Benmamoun; Hanaa Hachimi (AIMS Environmental Science, 2024)
The evolution of mega-ships and maritime alliances, in tandem with global changes, has intensified hub port competitiveness, increasing the need for innovation and adaptation, with a focus on sustainability. This study analyzed the competitiveness of the Mediterranean maritime hub port with Northern European ports. It provided a comprehensive analysis of the competitiveness of ten leading international hub ports in the Mediterranean and Northern Europe. Using the Hybrid F-AHP TOPSIS method, this research first identified and assigned weights to 10 criteria across five categories of port competitiveness from a shipping liner perspective in the Mediterranean and Northern Europe. It then ranked those ten leading ports based on the weighted criteria. The results showed that handling cost, operational efficiency, and infrastructure were the main factors for defining a competitive hub port, with growing emphasis on sustainability considerations. The results also highlight that Tangier Med, Algeciras, and Port Said were the leading ports in the region, excelling in technical efficiency and maritime costs compared to Northern European ports. The analysis further provided a holistic overview of competitiveness in the region, identifying the strengths and opportunities of each port based on 5 aspects with a special focus on the hub ports of the Southern Mediterranean. This research offers valuable insights for maritime shippers and port authorities in understanding hub port performance and competitiveness in a sustainable context.